Mecanismos de simplificación administrativa a la luz de las recientes modificaciones a la Ley del Procedimiento Administrativo General, Ley 27444, y la reciente Ley de Prevención y Eliminación de Barreras Burocráticas, Decreto Legislativo 1256 - Maraví, Milagros (Pontificia Universidad Católica del Perú, 2017)
In this academic article, the author analyzes the administrative simplification mechanisms implemented in the Law of General Administrative Procedure, 27444, as amended by Legislative Decree 1272, and in the recent Law of Prevention and Elimination of Bureaucratic Barriers, Legislative Decree 1256. Thus, it can be seen that both laws have taken into account the recommendations of the Organisation for Economic Co-operation and Development (OECD) in order to (i) alleviate the burdens imposed on the citizens in the development of administrative procedures, (ii) empower the Office of the President of the Council of Ministers in order to implement administrative simplification measures and to monitor compliance by entities, and (iii) eliminate bureaucratic barriers in our legal framework.

En el presente artículo, la autora analiza los mecanismos de simplificación administrativa implementados en la Ley del Procedimiento Administrativo General, Ley 27444, modificada por el Decreto Legislativo 1272, y en la reciente Ley de Prevención y Eliminación de Barreras Burocráticas, Decreto Legislativo 1256. Así, se podrá evidenciar que ambas normas han tomado en consideración las recomendaciones de la Organización para la Cooperación y el Desarrollo Económicos (OCDE) para (i) alivianar las cargas impuestas a los administrados en el desarrollo de los procedimientos administrativos, (ii) empoderar a la Presidencia del Consejo de Ministros para que implemente medidas adicionales de simplificación administrativa y supervise el cumplimiento por parte de las entidades, y (iii) eliminar las barreras burocráticas en nuestro ordenamiento.
Mechanisms for administrative simplification in light of recent amendments to the General Administrative Procedure Law, 27444, and the recent Law of Prevention and Elimination of Bureaucratic Barriers, Legislative Decree 1256
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.00